2005
DOI: 10.1124/dmd.105.006262
|View full text |Cite
|
Sign up to set email alerts
|

DISPOSITION OF ORAL AND INTRAVENOUS PRAVASTATIN IN MRP2-DEFICIENT TRRATS

Abstract: ABSTRACT:The aim of this study was to characterize the role of the efflux transporter Mrp2 (Abcc2) in the pharmacokinetics of orally and intravenously administered pravastatin in rats. Eight Mrp2-deficient TR ؊ rats and eight wild-type rats were given an oral dose of 20 mg/kg pravastatin. Four TR ؊ animals and four wild-type animals were studied after intravenous administration of pravastatin (5 mg/kg). The TR ؊ rats showed a 6.1-fold higher mean area under the plasma concentration-time curve (AUC) of pravasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 25 publications
1
39
1
Order By: Relevance
“…Recent in vitro studies indicated that organic anion transporter 3 (OAT3) expressed at the basolateral membrane of renal proximal tubule epithelial cells is predominantly involved in renal uptake of both pravastatin and olmesartan (Hasegawa et al 2002;Yamada et al 2007). The drug-drug interaction via OAT3 between pravastatin and olmesartan may account for the reduction of olmesartan renal excretion in the co-administration phase; however, the interaction via MRP2, which also is expressed in the kidney, cannot be ruled out (Kivistö et al 2005;Nakagomi-Hagihara et al 2006). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent in vitro studies indicated that organic anion transporter 3 (OAT3) expressed at the basolateral membrane of renal proximal tubule epithelial cells is predominantly involved in renal uptake of both pravastatin and olmesartan (Hasegawa et al 2002;Yamada et al 2007). The drug-drug interaction via OAT3 between pravastatin and olmesartan may account for the reduction of olmesartan renal excretion in the co-administration phase; however, the interaction via MRP2, which also is expressed in the kidney, cannot be ruled out (Kivistö et al 2005;Nakagomi-Hagihara et al 2006). …”
Section: Resultsmentioning
confidence: 99%
“…Taking these into consideration, increased AUC and decreased CL t /F of olmesartan in the co-administration phase are unlikely to result from the inhibition of CYP-mediated metabolism of olmesartan by pravastatin. However, possible interaction via other transporters, multidrug resistance-associated protein 2 (MRP2) in particular, cannot be negligible, because pravastatin and olmesartan are also a substrate of MRP2, and this transporter is reported to be involved in their biliary excretion (Kivistö et al 2005;Nakagomi-Hagihara et al 2006). No significant intergenotypic differences in the mean Ae 0-24 and CLr 0-24 values of olmesartan were observed in both the single-dose and co-administration phases; however, these values in the single-dose phase were decreased after co-administration of pravastatin, irrespective to SLCO1B1 status (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the study day, the overnight (12 h) fasted rats of group I were orally treated with an aqueous PVS solution (treatment A) equivalent to 20 mg/kg while those of Group II were orally administered with E-F8 cubosomes (treatment B) at the same dose (Kivistö et al, 2005).…”
Section: Oral Administration Of Treatments and Sample Collectionmentioning
confidence: 99%
“…Our results showed that coadministration of paroxetine markedly decreased the hepatic uptake of pravastatin ( Figure 7G), which may become a reason that paroxetine weakened the cholesterol-lowering effects of pravastatin ( Figure 1C). Although the transport of pravastatin from the blood into the bile is mainly mediated by Mrp2 [46,47] , data from QT-PCR showed that drug treatment did not disrupt the effects of DM on Mrp2 mRNA levels, excluding the possibility that Mrp2 mRNA levels might explain the increased exposure to pravastatin by coadministration of paroxetine.…”
Section: Discussionmentioning
confidence: 99%